The Role of Folklore and Ethnographic Communities of the Uzbek Intangible Cultural Heritage in the Musical Art - Ugli, Orifjonov Husniddin Sohibjon (International Journal on Integrated Education, 2023)
This article discusses folklore and ethnographic communities that are the heritage of Uzbek intangible music, and their development. Intangible musical heritage widely covers the history of folklore, as well as the process of education and upbringing in musical folklore. Examples of folk songs are given.